Recent trends in pediatric bacterial meningitis in Japan, 2016–2018 – S. agalactiae has been the most common pathogen. Issue 10 (October 2020) - Shinjoh, Masayoshi; Yamaguchi, Yoshio; Furuichi, Munehiro; Yaginuma, Mizuki; Takahashi, Takao; Iwata, Satoshi
Abstract: Background: Haemophilus influenzae type b (Hib) vaccine and pneumococcal conjugated vaccine (PCV) have been widely used since 2010 in Japan. The overall incidence of bacterial meningitis decreased thereafter. Streptococcus agalactiae has become the main organism. Objectives: The purpose of the present study was to investigate the incidence rate per 1000 admissions of bacterial meningitis and the change in causative organisms in subsequent years. Methods: A cross-sectional, multicenter, non-interventional retrospective study regarding pediatric bacterial meningitis was conducted in Japan in 2019. We analyzed the epidemiological and clinical data for 2016–2018, and compared the information obtained in our previous nationwide survey database. We also investigated the risk factors for disease outcome. Results: In the 2016–2018 surveys, 197 patients from 153 hospitals from all prefectures were evaluated. S. agalactiae (0–3 months, 39%), Streptococcus pneumoniae (2–112 months, 20%), and E. coli (0–136 months, 13%) were the main organisms. The total number of patients hospitalized with bacterial meningitis per 1000 admissions decreased from 1.00 to 1.68 in 2000–2010 to 0.38 in 2013–2015, bu remained stable thereafter (0.35–0.40 in 2016–2018). Only one case with Neisseria meningitidis was reported. Nine cases with death were reported, including four cases with S. agalactiae . Risk factors for death and sequelae were consciousness disturbance, duration of convulsion, low CSF glucose levels, and disuse of dexamethasone (p < 0.05). Conclusions: The incidence in pediatric bacterial meningitis remained low, and S. agalactiae remains the most common cause of bacterial meningitis in Japan since 2012. S. pneumoniae is the most common cause after 3 months of age.